Effect of Choline Forms and Gut Microbiota Composition on Trimethylamine-N-Oxide Response in Healthy Men - Cho, Clara E.; Aardema, Niklas D. J.; Bunnell, Madison L.; Larson, Deanna P.; Aguilar, Sheryl S.; Bergeson, Janet R.; Malysheva, Olga V.; Caudill, Marie A.; Lefevre, Michael (Nutrients, 2020)
Background: Trimethylamine-N-oxide (TMAO), a choline-derived gut microbiota-dependent metabolite, is a newly recognized risk marker for cardiovascular disease. We sought to determine: (1) TMAO response to meals containing free versus lipid-soluble choline and (2) effects of gut microbiome on TMAO response. Methods: In a randomized, controlled, double-blinded, crossover study, healthy men (n = 37) were provided meals containing 600 mg choline either as choline bitartrate or phosphatidylcholine, or no choline control. Results: Choline bitartrate yielded three-times greater plasma TMAO AUC (p = 0.01) and 2.5-times greater urinary TMAO change from baseline (p = 0.01) compared to no choline and phosphatidylcholine. Gut microbiota composition differed (permutational multivariate analysis of variance, PERMANOVA; p = 0.01) between high-TMAO producers (with ≥40% increase in urinary TMAO response to choline bitartrate) and low-TMAO producers (with <40% increase in TMAO response). High-TMAO producers had more abundant lineages of Clostridium from Ruminococcaceae and Lachnospiraceae compared to low-TMAO producers (analysis of composition of microbiomes, ANCOM; p < 0.05). Conclusion: Given that phosphatidylcholine is the major form of choline in food, the absence of TMAO elevation with phosphatidylcholine counters arguments that phosphatidylcholine should be avoided due to TMAO-producing characteristics. Further, development of individualized dietary recommendations based on the gut microbiome may be effective in reducing disease risk